Sistem Pakar Dalam Penentuan Minat dan Bakat Anak Usia Taman Kanak-Kanak Menggunakan Metode Dempster Shafer - Devaus, Lea; Amaliah, Yusni; Gusmana, Roman (Journal of Big Data Analytic and Artificial Intelligence, 2024)
Early childhood education relates to the teaching of children from birth up to the age of six, which prepares children for further education by providing educational stimulation to aid physical and spiritual growth. Thus, it is necessary a system to help parents learn their children's interests and talents to direct and develop their potential, especially in the arts. Dempster Shafer is a mathematical theory of evidence based on belief function and plausible reasoning to combine discrete pieces of information to calculate the probability of an event. The results show that children's interest and talent in art at Paud Pelangi Desa Sedulun consists of 5 types: Mosaic Art, Acting Art, Music Art, Montage Art, and Painting Art. Manual calculations and computerized tests produce the highest percentage value and the final conclusion. Determining children's interests and talents from the input of behavioral criteria generates a final assessment that helps children's development in the arts.